Competing for father's love? The politics of central government agency termination in China. Issue 4 (27th March 2019) - Chen, Sicheng; Christensen, Tom; Ma, Liang
Abstract : It is well known that public agencies are nearly immortal, but what explains their termination? This article argues that apart from conventional antecedents, political salience defined by top leaders largely shapes government agencies' life cycle. In one of the first large‐N analyses of agency termination in a non‐Western authoritarian regime, we used longitudinal data for the central apparatus in China from 1949 to 1976 to test this hypothesis. We specifically used Chairman Mao's written directives to measure political salience and found that agencies that received more directives were less likely to be terminated. In contrast, agencies less attended to the boss were less likely to survive major restructurings. We also found that peripheral agencies (e.g., smaller, lower‐ranking agencies with noncore functions) benefited more from leaders' attention. We compare the results with the existing literature and suggest some theoretical and policy implications.